Analyzing Air Traffic Control Failures In Aviation Incidents And Accidents Through The HFACS Framework - Hendro Eko Saputro; Elfi Amir; Rany Adiliawijaya Putriekapuja (International Journal of Health Engineering and Technology, 2026)
Aviation safety depends heavily on precise interaction between pilots and Air Traffic Control (ATC), yet failures within that interaction remain a recurring contributing factor in civil aviation accidents and incidents. This study aims to identify and analyze patterns of ATC-related failure across a set of historically significant aviation accidents and incidents, and to derive implications for global aviation safety improvement. A qualitative literature review design was employed, drawing on official investigation reports, safety databases, and peer-reviewed journal articles concerning five representative events—Tenerife (1977), Zagreb (1976), Uberlingen (2002), Linate (2001), and Jakarta Halim (2016)—synthesized through directed content analysis guided by the Human Factors Analysis and Classification System (HFACS) and Reason's Swiss Cheese Model. The findings reveal that communication breakdowns, non-standard phraseology, controller work overload, limitations in surveillance technology, and weak inter-unit coordination constitute recurring causal patterns behind ATC-related accidents/incidents. The study concludes that enhancing aviation safety requires stricter phraseology standardization, strengthened Crew/Team Resource Management training for controllers, and sustained investment in surface radar and conflict-alert technologies.